2018
DOI: 10.1530/joe-17-0200
|View full text |Cite
|
Sign up to set email alerts
|

Cell-secreted vesicles containing microRNAs as regulators of gamete maturation

Abstract: Mammalian gamete maturation requires extensive signaling between germ cells and their surrounding somatic cells. In the ovary, theca cells, mural granulosa cells, cumulus cells and the oocyte all secrete factors throughout follicle growth and maturation that are critical for ovulation of a high-quality oocyte with the competence to develop into an embryo. Similarly, maturation of sperm occurs as it transits the epididymis during which epididymal epithelium and sperm exchange secretory factors that are required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 62 publications
0
48
0
1
Order By: Relevance
“…A communication between embryos and maternal uterine milieu through secreting signals is required for proper mammalian development (O'Neill, ). Recent studies observed that EVs are secreted from various somatic cells including human embryonic stem cell (Mardpour et al, ), induced pluripotent stem cell (Bobis‐Wozowicz et al, ), ovarian follicle (da Silveira et al, ), and even embryos (Qu et al, ). Our previous study also demonstrated that membrane budding microvesicles from outgrowth embryos improved developmental competence in vitro and the implantation potential of cocultured embryos in utero as well (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A communication between embryos and maternal uterine milieu through secreting signals is required for proper mammalian development (O'Neill, ). Recent studies observed that EVs are secreted from various somatic cells including human embryonic stem cell (Mardpour et al, ), induced pluripotent stem cell (Bobis‐Wozowicz et al, ), ovarian follicle (da Silveira et al, ), and even embryos (Qu et al, ). Our previous study also demonstrated that membrane budding microvesicles from outgrowth embryos improved developmental competence in vitro and the implantation potential of cocultured embryos in utero as well (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These compositions can be transferred between different types of cells and influence biological activities . Recently, some studies uncovered the potential function of exosomes derived from FF as carriers of miRNAs in steroidogenesis, follicular development and other pathological conditions …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Recently, some studies uncovered the potential function of exosomes derived from FF as carriers of miRNAs in steroidogenesis, follicular development and other pathological conditions. [24][25][26][27] Although proteome and peptidome were identificated in human FF, [28][29][30][31][32][33] little was known about the proteomic analysis of exosomes in follicular fluid and their potential roles in follicular development and reproduction-related disorders. Therefore, we used an TMT-tagged quantitative proteomic approach to compare the proteomic profile of exosomes derived from FF of PCOS and healthy women.…”
mentioning
confidence: 99%
“…In the ovary, from the theca cells, mural granulosa cells, cumulus cells, and oocyte secrete factors that are critical for ovulation of high‐quality oocyte, throughout follicle growth and oocyte maturation. Recent studies of a variety of species have uncovered the presence of cell‐secreted vesicles in follicular fluid . These cell‐secreted vesicles contain small non‐coding regulatory RNAs called microRNAs, which can be shuttled between maturing gametes and surrounding somatic cells .…”
Section: Molecular Markers Related To Oocyte Qualitymentioning
confidence: 99%
“…However, recent studies suggest that microRNAs in cell‐secreted vesicles are involved in oocyte maturation. These microRNAs involved in gamete maturation are potential therapeutic targets and diagnostic markers associated with fertility …”
Section: Molecular Markers Related To Oocyte Qualitymentioning
confidence: 99%